2015
DOI: 10.1097/nen.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of HTLV-1–Specific Cytotoxic T Lymphocytes in the Spinal Cords of Patients With HTLV-1–Associated Myelopathy/Tropical Spastic Paraparesis

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 37 publications
1
63
0
1
Order By: Relevance
“…Pro‐inflammatory cytokines, such as tumor necrosis factor‐α, interferon (IFN)‐γ and interleukin (IL)‐1β, were detected in perivascular infiltrating cells . There is direct evidence that HTLV‐1‐infected CD4+ T cells have been observed within spinal cord lesions, and CD8+ T cells directed against HTLV‐1 antigens accumulate in the CSF and spinal cord lesions . Importantly, HTLV‐1 is only observed in T cell infiltrates within spinal cord lesions, but there is no convincing evidence showing that cells normally resident in the central nervous system (CNS) become infected .…”
Section: Ham/tsp Is Not a Simple Infection Of Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro‐inflammatory cytokines, such as tumor necrosis factor‐α, interferon (IFN)‐γ and interleukin (IL)‐1β, were detected in perivascular infiltrating cells . There is direct evidence that HTLV‐1‐infected CD4+ T cells have been observed within spinal cord lesions, and CD8+ T cells directed against HTLV‐1 antigens accumulate in the CSF and spinal cord lesions . Importantly, HTLV‐1 is only observed in T cell infiltrates within spinal cord lesions, but there is no convincing evidence showing that cells normally resident in the central nervous system (CNS) become infected .…”
Section: Ham/tsp Is Not a Simple Infection Of Cnsmentioning
confidence: 99%
“…Notably, more than half of the CXCR3+ T cells in the CSF of HAM/TSP patients are CD8+ T cells . It has been shown that CD8+ cytotoxic T lymphocytes, particularly HTLV‐1‐specific cytotoxic T lymphocytes, have a high potential for secreting IFN‐γ, and are abnormally elevated in the CSF and spinal cord lesions . Therefore, CXCL10 production by astrocytes might further boost the trafficking of CXCR3+ CCR4+ infected CD4+ T cells as well as CXCR3+ CD8+ cytotoxic T lymphocytes that secrete IFN‐γ, leading to a positive feedback inflammatory loop.…”
Section: Importance Of Cross‐talk Between Infected T Cells and Astrocmentioning
confidence: 99%
“…This view of disease pathogenesis is most consistent with data generated from immunohistochemistry studies which demonstrate both CD4 (+) and CD8 (+) T lymphocytic infiltrates in spinal cord tissues during early stages of disease, with increasing dominance of CD8 (+) T lymphocytes and macrophages over the course of the illness (Umehara et al, 1993) (Abe et al, 1999) (Kubota et al, 1998). Recently, specific interactions between HTLV-1 Tax positive CD4 (+) T lymphocytes and virus-specific CTLs were demonstrated in spinal cord tissues of HAM/TSP patients using confocal laser scanning microscopy (Matsuura et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…13 CD4 + T lymphocytes are the predominant target of HTLV-1 infection, 14 which are early detected in spinal cord lesions. 15,16 Some research groups have shown that the risk for HAM/TSP development positively correlates with HTLV-1 proviral load in PBMCs. 17,18 The control of HTLV-1 infection in vivo has not been fully clarified yet.…”
mentioning
confidence: 99%